Nasjonal reproduksjon og fornying — kongelige snap shot - Bjorli, Trond (Tidsskrift for kulturforskning, 2016)
Abstract Photographic imagery became modernized during the first decade of the 20th Century. In Norway this coincided with the nation's break with the Union between Sweden and Norway. This conjunction of events highly fused both the photographic renewal and the modernization of the national discourse. Overnight this found its most important visual expressions in modernized photographic imagery. The article uses some of Jacques Rancière's ideas presented in The Politics of Aesthetics: The Distribution of the Sensible (english version 2004) to discuss how the Norwegian photographer Anders Beer Wilse's (1865-1949) photographic imagery can be seen to open new fields for identity politics in Norway during the early 20th Century. In this, the article concentrates its analysis on four royal photographs that led to four richly illustrated books about the Norwegian nation during the years 1905 to 1908.